Pengaruh Konten Edukasi Karir Di Media Sosial Terhadap Kesiapan Kerja Mahasiswa Tingkat Akhir: Studi Kasus Konten Kreator Vina Muliana - Gozali, Ramadhan Saputra; Malik Sayuti, Abdul (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
Purpose – This study analyzes the effect of career education content by Vina Muliana on the work readiness of final year students. Novelty – This study uses test variables in the form of work readiness as the dependent variable and career education content as the independent variable where the study is still very limited and has not been carried out in many existing similar studies, the approach used in this study is quantitative methods, where this method has been used very little in the context of similar research, using final year students as research subjects can certainly offer a new perspective on the study being conducted. Method – The approach in this study uses quantitative methods, where data obtained through primary data in the form of questionnaires distributed to target respondents using purposive sampling on 405 respondents will be tested using simple linear regression analysis to be able to test the effect between the test variables in this study using IBM SPSS software. Findings – The results of this study indicate that career education content uploaded by Vina Muliana has a positive influence on the job readiness of final year students. Limitations and Implications – This study has limitations in the form of coverage represented by 24 provinces out of 38 provinces throughout Indonesia so that the coverage area can be expanded in future research, but this study can provide implications for final year students to make career education content uploaded by Vina Muliana as a medium to prepare themselves for work to be able to face the career world in the future.